Pengaruh Model Pembelajaran SAVI (Somatic, Auditory, Visual, Intelectual) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Korespondensi di SMK Negeri 10 Surabaya - Putri Rikhmah Nadhiah; Siti Sri Wulandari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This study aims to know the difference from application of conventional method oral models that compared to Somatic, Auditory, Visual, dan Intellectual (SAVI) models in basic competiences learning about office communication of Grade X OTKP SMKN 10 Surabaya students. This kind of study is quasi experimental design with non-equivalent control group design.. The sample that used are students of class X OTKP 3 as a control class and class X OTKP 4 as an experimental class. Result of the analysist, found significant difference from experimental class study result where have 28,06 (gain score) that obtained from 78,06 (mean of postest) that reduced by 50 (mean of pretest). While for control class have 20,42 (gain score) that obtained from 58,18 (mean of postest) reduced by 47,78 (mean of pretest).  Then, based on the t-test on the psychomotor values of students, it was obtained that tcount was 4,498 with a significance level of 00 (0.00) and a confidence level of 95% Î± = 0.05 with df = N-2 = 70, then a ttable = 1.994 was obtained. It can be concluded from the results of the t-test that H0 is rejected and H1 is accepted. Thus it was concluded that the difference after being applied Somatic, Auditory, Visual, and Intellectual (SAVI) was an increase in students results and speaking skills of class X OTKP students on the basic competiences learning about office communication